2015
DOI: 10.2215/cjn.06680714
|View full text |Cite
|
Sign up to set email alerts
|

CKD and Its Risk Factors among Patients with Cystinuria

Abstract: Background and objectives Cystinuria is an autosomal recessive disorder affecting renal cystine reabsorption; it causes 1% and 8% of stones in adults and children, respectively. This study aimed to determine epidemiologic and clinical characteristics as well as comorbidities among cystinuric patients, focusing on CKD and high BP.Design, setting, participants, & measurements This retrospective study was conducted in France, and involved 47 adult and pediatric nephrology and urology centers from April 2010 to Ja… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
67
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(84 citation statements)
references
References 34 publications
9
67
1
3
Order By: Relevance
“…Indeed, a French cohort study of 442 patients showed that 26.7% had CKD and only 22.5% had a (normal) estimated glomerular filtration rate (eGFR) of >90 ml/min/1.73 m 2 ; a history of staghorn stones and multiple open surgical stone procedures constituted a relevant risk factor for CKD and nephrectomy 209 . Accordingly, patients should be monitored for urinary pH and volume.…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…Indeed, a French cohort study of 442 patients showed that 26.7% had CKD and only 22.5% had a (normal) estimated glomerular filtration rate (eGFR) of >90 ml/min/1.73 m 2 ; a history of staghorn stones and multiple open surgical stone procedures constituted a relevant risk factor for CKD and nephrectomy 209 . Accordingly, patients should be monitored for urinary pH and volume.…”
Section: Diagnosis Screening and Preventionmentioning
confidence: 99%
“…In a recent UK study (16), the level of renal impairment observed was similar across all genotypes. Recently, a recent large retrospective study conducted by the French Cystinuria Group (27) showed that 5 (1.1%) of 442 patients with cystinuria progressed to end stage renal disease at a median age of 35.0 (11.8–70.7) years. Multivariate analyses revealed that progression to chronic kidney disease was associated with age, hypertension, severe damage of renal parenchymal defined as a history of partial or total nephrectomy, and so on (27).…”
Section: Discussionmentioning
confidence: 99%
“…Among the Third National Health and Nutrition Examination Survey (NHANES III) participants, a history of kidney stones in subjects with body mass index (BMI) ≥ 27 kg/m 2 increased the probability of having an estimated glomerular filtration rate (eGFR) < 60 ml/min/1.73 m 2 compared to overweight non-stone formers [8]. Stone formers with cystinuria, uric acid or struvite stones, renal tubular acidosis, or chronic bowel disorders frequently manifest decreased GFR, and CKD/ESRD [9, 10]. Standard Roux-en-Y gastric bypass and malabsorptive types of bariatric surgery are both associated with an increased risk for stones and CKD [11].…”
Section: Questions and Consensus Statementsmentioning
confidence: 99%